2003
DOI: 10.1002/qua.10706
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the adsorption of ethylene on alkali‐exchanged zeolites

Abstract: ABSTRACT:The structures of alkali-exchanged faujasite (X-FAU, X ϭ Li ϩ or Na ϩ ion) and ZSM-5 (Li-ZSM-5) zeolites and their interactions with ethylene have been investigated by means of quantum cluster and embedded cluster approaches at the B3LYP/6-31G (d, p) level of theory. Inclusion of the Madelung potential from the zeolite framework has a significant effect on the structure and interaction energies of the adsorption complexes and leads to differentiation of different types of zeolites (ZSM-5 and FAU) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In this study, the total Madelung potential is represented by 649 explicit charges within 120 pm to the quantum cluster and 1210 surface charges. Previous studies [29][30][31][32][33]64] revealed that the calculated adsorption properties agree well with experimental estimates, suggesting that the SCREEP embedded approach is a sufficiently accurate and practical model for studying reaction mechanisms on zeolites. In this current investigation, only the active site region (H 2 SiOAl(OH) 2 O(H)SiH 2 ) and the adsorbate molecule were allowed to relax, while the remaining atoms were kept fixed at the experimental structure.…”
Section: Computational Detailssupporting
confidence: 65%
“…In this study, the total Madelung potential is represented by 649 explicit charges within 120 pm to the quantum cluster and 1210 surface charges. Previous studies [29][30][31][32][33]64] revealed that the calculated adsorption properties agree well with experimental estimates, suggesting that the SCREEP embedded approach is a sufficiently accurate and practical model for studying reaction mechanisms on zeolites. In this current investigation, only the active site region (H 2 SiOAl(OH) 2 O(H)SiH 2 ) and the adsorbate molecule were allowed to relax, while the remaining atoms were kept fixed at the experimental structure.…”
Section: Computational Detailssupporting
confidence: 65%
“…The simple naked M + C 2 H 4 models obviously overestimate as compared to the interaction of C 2 H 4 in real zeolite system due to the large electrostatic field generated by the naked metal cation. [49] This shows that the oxygen in zeolite fragment cluster is strongly coordinated with smaller cation, as the same observation is obtained the Sanderson electronegativity index of monovalent ion exchanged nano-porous Faujasite.…”
Section: Adsorption Of C2-hydrocarbon In Nano-porous Zeolite Faujasitesupporting
confidence: 74%
“…Figure 1) are calculated based on the same theory. Previously, Ketrat and Limtrakul [49] demonstrated the interactions of ethylene in Faujasite type zeolite with B3LYP/6-31G (d,p) level of theory. In addition to this, various DFT functional such as B3P86 [50], PW91, PBE, etc.…”
Section: Resultsmentioning
confidence: 99%
“…1) to reproduce the long-range electrostatic field from the extended zeolite framework. Using two sets of point charges in such a way has already been employed in studies of several zeolite systems [24,25,27].…”
Section: Methods and Cluster Modelsmentioning
confidence: 99%
“…Furthermore, they often introduce an unrealistic perfect symmetry into the model. Hybrid methods, such as the embedded cluster or combined quantum mechanics/molecular mechanics (QM/MM) methods [23][24][25][26][27][28][29][30][31], as well as the more general ONIOM ('Our-own-N-layer integrated molecular orbital + molecular mechanics') method [32][33][34][35][36][37][38][39][40][41][42] provide a cost effective computational strategy for including the effects of the zeolite framework.…”
Section: Introductionmentioning
confidence: 99%